Media Systems and Communication Policies in Latin America - Guerrero, M.; Márquez-Ramírez, M.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Media Systems and Communication Policies in Latin America proposes, tests and analyses the liberal captured model. It explores to what extent to which globalisation, marketization, commercialism, regional bodies and the nation State redefine the media's role in Latin American societies.
Keywords: Social policy; Cultural policy; Ethnology—Latin America; Political science; Communication; United States—Politics and government; Social Policy; Cultural Policy and Politics; Latin American Culture; Political Science; Media Studies; US Politics